In situ generated silver nanoparticles embedded in polyethersulfone nanostructured membranes (Ag/PES) for antimicrobial decontamination of water. Issue 11 (14th August 2021) - Patala, Rapelang; Nyoni, Hlengilizwe; Mamba, Bhekie B; Liu, Dan; Gui, Jianzhou; Kuvarega, Alex T
Abstract: BACKGROUND: The general performance of polymeric membranes is hindered by the build‐up of microbial foulants both on the surface and inside the pores. This justifies the inclusion of antimicrobial agents within the membranes in order to circumvent the biofouling process. A nonsolvent‐induced phase separation process was used to fabricate the membranes following the in situ reduction of silver (Ag) in the polymer dope solution. Fourier transform infrared, atomic force microscopy (AFM), scanning and transmission electron microscopy, and drop shape analyzer were used to study different properties of the membranes. RESULTS: Based on the results of AFM and contact angle measurements, the inclusion of Ag nanoparticles (NPs) improved the membrane hydrophilicity. The disk diffusion method was applied to study the antimicrobial properties of the membranes. The fabricated Ag/ polyethersulfone (PES) membranes showed antimicrobial activity against representatives of both Gram‐positive and ‐negative bacteria, and this was confirmed by the zones of inhibition (11 mm for Escherichia coli ; 13 mm for Bacillus cereus ). From this a general proposed antimicrobial mechanism via the generation of reactive oxygen species (ROS) was provided. CONCLUSION: The fabricated Ag/PES membranes can perform a dual function of complete microbial inactivation and ultrafiltration of polluted water to provide better quality water with reduced membrane fouling. © 2021 Society of Chemical Industry (SCI).